2019
DOI: 10.3390/genes10120953
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Genetic Findings of Autosomal Recessive Bestrophinopathy (ARB)

Abstract: Mutations in BEST1 cause several phenotypes including autosomal dominant (AD) Best vitelliform macular dystrophy type 2 (BVMD), AD vitreo-retino-choroidopathy (ADVIRC), and retinitis pigmentosa-50 (RP50). A rare subtype of Bestrophinopathy exists with biallelic mutations in BEST1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Next-generation sequencing genetic analysis of 325 retinal degeneration associated genes was positive for a homozygous mutation in BEST1 , c.103G>A (p.Glu35Lys), which has been previously reported 39 41 and predicted to be damaging by Sift, PolyPhen, and CADD.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Next-generation sequencing genetic analysis of 325 retinal degeneration associated genes was positive for a homozygous mutation in BEST1 , c.103G>A (p.Glu35Lys), which has been previously reported 39 41 and predicted to be damaging by Sift, PolyPhen, and CADD.…”
Section: Resultsmentioning
confidence: 81%
“…19,[23][24][25][26][27][28][29][30] Indeed, multiple previous reports of p.Glu35Lys are all associated with autosomal recessive inheritance, without known parent carrier phenotypes. 39,40,41 A major limitation to our study is that parents were not routinely clinically examined in the absence of reported symptoms or a concerning vision history. In rare cases, pathogenic BEST1 variants are inherited in a semidominant fashion.…”
Section: Discussionmentioning
confidence: 99%
“…variant has previously been reported by Tian et al and Habibi et al, albeit in a homozygous state. [34,35] To the best of our knowledge, ours is the rst study to report this variant in a heterozygous state.…”
Section: Genetic Ndingsmentioning
confidence: 86%
“…Both studies further reinforce the need for increasingly diverse reference genome datasets to more accurately identify and interpret genomic variants in the context of rare disease. Other studies in this issue describe genotypic findings from specific ancestral cohorts, including a large genotypic study from Irish patients [9], descriptions of macular genetic disease associations in defined populations [10,11], and the description of detailed phenotypic presentations associated with specific genetic variants [12,13]. Interestingly, two of the studies in this issue describe findings that the same genetic variant can lead to extreme variability in phenotypic presentation.…”
mentioning
confidence: 99%